Ommatophoca rossii Gray 1844 - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Ommatophoca rossii Gray, 1844. Zool. Voy. H.M.S. "Erebus" and "Terror," 1:3. TYPE LOCALITY: "Antarctic ocean", restricted by Barrett-Hamilton (1902) to "pack ice, north of Ross Sea 68°S, 176°E ". DISTRIBUTION: Circumpolar, Antarctic pack ice, particularly King Haakon VII Sea. Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 331, DOI: 10.5281/zenodo.7359191